2000
DOI: 10.1159/000024312
|View full text |Cite
|
Sign up to set email alerts
|

β-Estradiol Suppresses T Cell-Mediated Delayed-Type Hypersensitivity through Suppression of Antigen-Presenting Cell Function and Th1 Induction

Abstract: Background: Although an immunomodulatory role for estrogens has long been demonstrated by experimental and clinical observations, the mechanism by which estrogens exert their effect on T cells has not been clearly defined. Methods: In this study we analyzed the effects of β-estradiol (E2), at its contraceptive dose, on the delayed-type hypersensitivity (DTH) to purified protein derivatives (PPD) and associated immune response in female mice. Results: E2 treatment decreased PPD-specific DTH response, which coin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…Authors speculated that these effects were mediated not only through ER, as it had been established earlier (74)(75)(76), but also via non-ER pathways. The above-mentioned data correspond with results showing that estradiol treatment of adult mice decreased leukocyte numbers in the draining lymph nodes from the injected limb during the DTH response (77).…”
Section: Phytoestrogens Gender and Allergic Responsesupporting
confidence: 88%
“…Authors speculated that these effects were mediated not only through ER, as it had been established earlier (74)(75)(76), but also via non-ER pathways. The above-mentioned data correspond with results showing that estradiol treatment of adult mice decreased leukocyte numbers in the draining lymph nodes from the injected limb during the DTH response (77).…”
Section: Phytoestrogens Gender and Allergic Responsesupporting
confidence: 88%
“…Innate immunity and macrophages have, therefore, been suggested to play a role (17). Estrogen has been reported to suppress T cell-dependent DTH and activation of inflammatory cells producing TNF-␣ and IFN-␥ (51)(52)(53)58). Our data suggest a downregulation of the Th1 response associated to DNB colitis as reflected by decreased IFN-␥ mRNA expression 14 days postcolitis in 17␤-estradiol-treated mice.…”
Section: Discussionmentioning
confidence: 52%
“…The existence of such a regulatory mechanism has been described in models of T cell-mediated delayedtype hypersensitivity, where estrogen has been found to suppress T-cell proliferation through targeting of antigen-presenting cells (51,52). Similarly, previous reports from our laboratory demonstrated that estrogen represses stromal cell-soluble M-CSF production through targeting of IL-1-and TNF-producing bone marrow cells, rather than through a direct effect on mature stromal cells (16,27).…”
Section: Sham Ovx Ovx Estrogen T Cells T Cells T Cellsmentioning
confidence: 53%